Functioning of Hospitals: Vital in Promoting Good Health and Well-Being - Dr. Radhika Kapur, (International Journal of Preventive Medicine and Health (IJPMH), 2024)
The hospitals are regarded as one of the prominent organizations, which have the primary goals of promoting good health and well-being of the individuals. This needs to be focused on physically and psychologically. The individuals, belonging to all age groups are experiencing different types of health problems and illnesses. Hence, they make visits to hospitals to get these treated. The medical practitioners and health care specialists need to make sure, they treat these in a well-ordered and disciplined manner. The measures are required to be put into practice appropriately in order to promote functioning of the hospitals in a satisfactory manner. The individuals are required to be well-versed in terms of different types of pioneering methods and materials in the implementation of job duties and responsibilities. Furthermore, it is necessary for the individuals to be well-versed in terms of traits of morality, ethics, diligence and conscientiousness. These are the key in enabling the individuals to cope with different types of dilemmas and challenging situations. Furthermore, they will achieve desired goals and objectives. As a consequence, they will render an important contribution in leading to overall functioning of hospitals in a well-ordered manner. Therefore, functioning of hospitals is vital in promoting good health and well-being. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of functioning of hospitals, measures to be implemented in promoting functioning of hospitals and advantages of promoting functioning of hospitals.